2021
DOI: 10.3889/oamjms.2021.6631
|View full text |Cite
|
Sign up to set email alerts
|

Association between Serum Brain-derived Neurotrophic Factor and 25-OH Vitamin D Levels with Vitamin D Receptors Gene Polymorphism (rs2228570) in Patients with Autoimmune Thyroiditis and Hypothyroidism

Abstract: BACKGROUND: Different polymorphisms in Vitamin D receptors (VDRs) have an important role in autoimmune thyroiditis (AIT) risk. Hashimoto’s thyroiditis (HT) is the most recurrent autoimmune thyroid disorder. Patients with HT may suffer from cognitive impairment brain-derived neurotrophic factor (BDNF) which has been identified as an important growth factor that is involved in learning and memory. AIM: This study examined the linkage of VDR gene polymorphism (rs2228570) with blood serum levels of BDNF and 25-O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…They promote neuronal survival, axonal growth, and synaptic plasticity, facilitating recovery after injury. Additionally, we also observed a decrease in the level of neurotrophic factors in patients with thyroid pathology [31,32].…”
Section: огляд / Reviewmentioning
confidence: 74%
“…They promote neuronal survival, axonal growth, and synaptic plasticity, facilitating recovery after injury. Additionally, we also observed a decrease in the level of neurotrophic factors in patients with thyroid pathology [31,32].…”
Section: огляд / Reviewmentioning
confidence: 74%
“…It has been demonstrated that the thyroid hormone profoundly affects neurogenesis [6]. This can lead to the onset of neurological complications occurring from thyroid pathology [7][8][9][10]. The modern search for effective targeted therapy is based on existing transcriptome and proteome data [11].…”
Section: Introductionmentioning
confidence: 99%
“…Determination of the level of gene transcriptional activity is an essential index of the functional activity of cells [9], [10], [11], [12], [13]. Our previous studies show significant changes in the transcriptional profile and genetic variations in different pathological conditions [14], [15], [16], [17], [18], [19]. Changes in some genes expression of the innate and adaptive immune system play a vital role in the mechanisms of AU development.…”
Section: Introductionmentioning
confidence: 99%